Shoe-ing out the president - Abd Razak, Dzulkifli (2009)
IN a couple of days, the world will witness the inauguration of a new president. It is an event much awaited by the international community as a singularly historic moment besides putting to rest the effects of the Bush fatigue which was marked by an unprecedented range of notable failures, be it in diplomacy, wars, intelligence, science education, pollution control, immigration and, more recently, the economy. Indeed, the Pew Research Centre quoted a finding where almost twothirds of the people polled said they will remember the Bush administration for its failures. What is worse are the failed expectations after Bush took office, promising to change the tone of Washington, a promise of a better government and to unite rather than divide.